2014
DOI: 10.2310/8000.2013.131034
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the RAPID approach at the start of emergency medicine clerkship: an evaluation

Abstract: Background: The RAPID approach (Resuscitation, Analgesia and assessment, Patient needs, Interventions, Disposition) was developed as an approach to managing emergency department patients. It is a mental checklist to help trainees provide comprehensive care, addressing issues in priority. Its impact on trainee performance has not been assessed. Methods: Forty-two clerkship students were enrolled, with 21 students in each group. They received or did not receive the teaching intervention on an alternate basis. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…They may omit important information that is essential to comprehensive and timely ED patient management. Mnemonics techniques known as RAPID (Resuscitation, Analgesia and assessment, Patient needs, Interventions, Disposition) [ 3 ] and SNAPPS (Summarize history and findings, Narrow the differential; Analyze the differential; Probe preceptor about uncertainties; Plan management; Select case-related issues for self-study) have been developed as prompts for clinical clerks to present cases concisely yet thoroughly, but they are linear and exist at one given point in time [ 4 ]. This is far from the typical ED learning opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…They may omit important information that is essential to comprehensive and timely ED patient management. Mnemonics techniques known as RAPID (Resuscitation, Analgesia and assessment, Patient needs, Interventions, Disposition) [ 3 ] and SNAPPS (Summarize history and findings, Narrow the differential; Analyze the differential; Probe preceptor about uncertainties; Plan management; Select case-related issues for self-study) have been developed as prompts for clinical clerks to present cases concisely yet thoroughly, but they are linear and exist at one given point in time [ 4 ]. This is far from the typical ED learning opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey revealed that 86% of medical students thought the EM-OCP was unique compared to that of other specialties and 78% felt that more training was required beyond the current level of instruction. 11 Undergraduate medical curricula designed to improve OCP skills have utilized many modalities such as online learning, 6,12 didactic and small-group sessions, 1,5,13,14 video demonstrations and interpretation, 5,12,14 individualized coaching sessions, 12,14 selfand peer assessment, 5 and detailed guidelines with pocket cards. 1,13,15 Previous studies have evaluated the impact of an OCP curriculum on student performance by comparing end-of-rotation OCP assessment scores to previous cohorts' scores; 1 by examining a combination of daily encounter cards, self-assessments, and written examination scores; 13 or, most commonly, by implementing OCP assessment checklists.…”
mentioning
confidence: 99%
“…11 Undergraduate medical curricula designed to improve OCP skills have utilized many modalities such as online learning, 6,12 didactic and small-group sessions, 1,5,13,14 video demonstrations and interpretation, 5,12,14 individualized coaching sessions, 12,14 selfand peer assessment, 5 and detailed guidelines with pocket cards. 1,13,15 Previous studies have evaluated the impact of an OCP curriculum on student performance by comparing end-of-rotation OCP assessment scores to previous cohorts' scores; 1 by examining a combination of daily encounter cards, self-assessments, and written examination scores; 13 or, most commonly, by implementing OCP assessment checklists. 6,7,12,14,15 In EM, one study assessed a novel approach to patients in the emergency department (ED) using the RAPID (Resuscitation, Analgesia and assessment, Patient needs, Interventions, Disposition) method; 13 however, this approach differs from common practice in the ED.…”
mentioning
confidence: 99%
“…A recent study used a mnemonic based method called the RAPID approach (resuscitation, analgesia and assessment, patient needs, interventions, disposition) to provide medical students rotating through their emergency medicine (EM) clerkship with a mental checklist to provide comprehensive care for their patients . They used this checklist to work through theoretical ED cases in a small group format.…”
mentioning
confidence: 99%
“…Although, the RAPID approach showed promising results on the effectiveness of mnemonic‐based teaching, it did not solely focus on the discharge process or address if it had impact on the patients' understanding of their care. Given the success of previous studies and in an effort to improve our patients' understanding of their discharge diagnosis and treatment plan, we developed and evaluated a simple algorithm to guide resident physicians through the critical elements of ED discharge using the mnemonic “R2D2.” R2D2 stands for reassess the patient, recheck the workup, discuss the disposition plan with the attending physician, and finally discuss the discharge plan with the patient and family. The idea for this study originated with a think tank composed of EM faculty, including the faculty investigator, in which they identified the biggest impediments to a successful patient discharge and shared thoughts about potential solutions.…”
mentioning
confidence: 99%